Marine biological responses to abrupt climate change in deep time - Kießling, Wolfgang; Reddin, Carl James; Dowding, Elizabeth; Dimitrijevic, Danijela; Raja, Nussaïbah Begum; Kocsis, Ádám (Paleobiology, 2024)
Ancient changes in the biosphere, from organismic traits to wholesale ecosystem changes, can be aligned with climate forcing across the Phanerozoic. Clear examples of abrupt climate warming causing biodiversity crises are primarily found between the Permian and Paleogene periods. During these times, catastrophic events occurred, resembling the extreme climate scenarios projected for the near future. The paleobiologic literature around these events generally supports the hypothesis that abrupt climate change was a dominant trigger of extinction and/or ecological crisis. When climate change and climate history are considered, virtually all post-Paleozoic global biotic events can be confidently attributed to climatic change, with abrupt warming (hyperthermal events) leaving the most consistent fingerprint. The combined stress of deoxygenation and warming are sufficient to explain marine extinction patterns across most hyperthermal events. Although ocean acidification may have contributed, the direct role of pH on the extinction toll of organisms is not consistently demonstrated. Future research can enhance the correspondence between the magnitudes of climatic changes and their biological impacts, even though observed rates of change cannot currently be compared across different timescales. Mimicking multi-scale approaches in modern ecology, paleontological approaches to climate impact research will benefit from specifically targeting scaling relationships.